2005
DOI: 10.1007/s00417-005-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biometric methods for measuring the anterior chamber depth in the non-contact mode

Abstract: All the methods allow non-contact biometry, but the results might differ due to measuring principles inherent to the system, experience of the examiner and compliance of the patient. Partial coherence interferometry with the AC-Master offers the advantage of measurement exactly along the optical axis with the highest reproducibility and patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 18 publications
0
30
2
8
Order By: Relevance
“…Die Reproduzierbarkeit der einzelnen Geräte wurde bereits in einigen Studien belegt [5,7,10,15,19,24,26]. Sowohl Alter als auch Geschlechtsverteilung der hier erfassten Probanden entsprechen der typischen Zielgruppe für kammerwinkelgestützte pIOL [18].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Die Reproduzierbarkeit der einzelnen Geräte wurde bereits in einigen Studien belegt [5,7,10,15,19,24,26]. Sowohl Alter als auch Geschlechtsverteilung der hier erfassten Probanden entsprechen der typischen Zielgruppe für kammerwinkelgestützte pIOL [18].…”
Section: Diskussionunclassified
“…Alle Messungen der VKT mit dem Ultraschallbiomikroskopieverfahren (UBM) wurden mit einer Vorlaufstrecke durchgeführt. Als Vorlaufflüssig-keit wurde 0,9% NaCl-Lösung eingesetzt.Der IOLMaster ermittelt die epitheliale VKT automatisiert[15,24]. Zur VKTMessung mit dem Visante OCT wurde im hochaufgelösten Querschnittbild der Vorderkammer der Hornhautapex manuell bestimmt.…”
unclassified
“…Bu de¤erin 2'nin üzerinde olmas› ölçümün geçerli oldu¤unu, 1,6'n›n alt›nda olmas› ise güvenilir olmad›¤› anlam›na gelir. Görme aks›ndaki yo¤un opasiteler, hasta fiksasyonun iyi olmamas›, nistagmus gibi durumlar ölçümün güvenilirli¤ini azalt›rlar (8).…”
Section: Giriflunclassified
“…Eleftheriadis (13) çal›flmas›nda IOLMaster ile saptad›¤› aksiyel uzunluk ölçümlerini ultrasonik biyometriye göre daha yüksek bulmufltur. Yap›lan di¤er çal›flmalarda IOLMaster'›n immersiyon biyometriye benzer, hatta daha do¤ru aksiyel uzunluk ölçümü ald›¤› gösterilmifltir (14,15 (8). Moreno ve ark.…”
Section: Tart›flmaunclassified
“…Several studies also have indicated a high reproducibility in pentacam (Shankar et al, 2008;Amano et al, 2006;Barkana et al, 2005;Ambrosio, Alonso, Luz, & Coca Velarde, 2006;ODonnell & Maldonado-Codina, 2005;Khoramnia, Rabsilber, & Auffarth, 2007;Lam & Chen, 2007;Buehl, Stojanac, Sacu, Drexler, & Findl, 2006;Meinhardt, Stachs, Stave, Beck, & Guthoff, 2006). Thus, it is functional in screening and management of corneal diseases over time.…”
mentioning
confidence: 97%